A survey on configurations of current-limiting circuit breakers (CL-CB) - Gu, Chunyang; Wheeler, Patrick; Castellazzi, Alberto; Watson, Alan James; Effah, Francis Boafo (2016)
This paper presents a survey of topology configurations of current-limiting circuit breakers. Twelve different current-limiting topologies within four categories are detailed discussed and compared. It is concluded that active CL-CB may be a good choice for AC for its controllable reactive power capability to increase stability and multi-function protection.